Engaging youth in decision-making process via new media: a case of rural and urban youth in marginalized communities in Malaysia - Hassan, Shahizan (2016)
This paper presents the outcome of a study, which investigates the way in which youth in marginalized communities utilize new media to participate in the decision making process.It aims to identify issues commonly raised by the rural and urban youth.Data gathering for this study involves three phases – conducting focus group discussions with 51 participants from five states in Malaysia, developing new media portal for youth, and organising five intervention programmes involving 393 rural and urban youth of marginalized communities in Malaysia.The findings show that the youth are more interested to voice out issues related to social aspects, particularly issues related to quality of living.Other issues are freedom of speech and rising cost of living.However, there are also some differences in terms of the issues raised by the rural and urban participants, which are discussed at length in this paper.This study highlights the need for the government to take into account various issues raised by the youth in the decision and policy-making processes.